2020
DOI: 10.54112/bcsrj.v2020i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Metal Toxicity on Maze Seedlings Growth Traits

Abstract: Maize is an edible cereal crop that belongs to family Gramineae and use as an energy source for human and animals. In our country the industrial and municipal wastewater has been being used for irrigation purposes that contain heavy metals. These heavy metals affect production of maize crop and soil quality. The purpose of this study was to investigate the affect of different heavy metals on maize growth and to asses more tolerant and more sensitive maize variety. Different concentrations of Mn and Cr (0, 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Similarly, genotypic variation in crops and their morphological/physiological activity against HM uptake is a good criterion to evaluate the dose response. A study investigated five cultivars of maize and revealed that the genotype 31R88 was a more sensitive cultivar, while Neelum was a tolerant maize cultivar against Cr and Mn stress [ 23 ]. In the study of [ 24 ], the sorghum cultivar JS-2002 has shown a higher Cd tolerance potential due to its efficient antioxidant defense system than the sensitive Chakwal Sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, genotypic variation in crops and their morphological/physiological activity against HM uptake is a good criterion to evaluate the dose response. A study investigated five cultivars of maize and revealed that the genotype 31R88 was a more sensitive cultivar, while Neelum was a tolerant maize cultivar against Cr and Mn stress [ 23 ]. In the study of [ 24 ], the sorghum cultivar JS-2002 has shown a higher Cd tolerance potential due to its efficient antioxidant defense system than the sensitive Chakwal Sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…This perennial grass, native to Asia, has low input requirements and is responsible for CO 2 sequestration and storage in below ground organs, which in turn could be valuable for nutrient-depleted soil, especially due to the translocation of nutrients into the rhizomes after each growing season [ 6 , 7 , 8 ]. In terms of phytoremediation, there are reports indicating the phytoextraction potential of TMEs by this plant [ 9 , 10 , 11 ]. However, field trials on such contaminated soils have shown that phytoextraction is insufficient for mature plantations and crops should rather be used for the phytostabilisation process due to the low concentration of TMEs in the aboveground biomass [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water availability and temperature are the most common factors affecting plant establishment, regardless of species, varieties, and annual or perennial type [ 1 , 15 , 18 , 19 ]. Apart from these most common abiotic stress factors, there may be other stress factors in growing energy crops on marginal soils, such as pollutants, i.e., Trace Metal Elements (TMEs), Polycyclic Aromatic Hydrocarbons (PAH) [ 9 , 10 , 20 ], or nutrient deficiencies [ 12 , 13 ], which may cause a cross-reaction in the plants.…”
Section: Introductionmentioning
confidence: 99%
“…They have been identified in animals and humans, causing dangerous health conditions [44]. Even though heavy metal contamination is an environmental and health threat, it is also known that some heavy metals can be favorable to plant growth in trace amounts, such as copper, iron, manganese, magnesium, molybdenum, and zinc [43,45]. When in the soil or irrigation water, the plant can uptake the heavy metals and they will be available in the plant; therefore, using nonedible plants may be useful to reduce the heavy metal concentration in the environment and concentrate on the plant.…”
Section: Introductionmentioning
confidence: 99%
“…When in the soil or irrigation water, the plant can uptake the heavy metals and they will be available in the plant; therefore, using nonedible plants may be useful to reduce the heavy metal concentration in the environment and concentrate on the plant. However, in the case of edible plants, the heavy metals can biomagnify [43,45]. Elements such as sodium, calcium, and magnesium can be used to calculate the sodium adsorption ratio (SAR), which indicates the salinity present in a sample and can indicate whether a water sample is suitable for irrigation [20].…”
Section: Introductionmentioning
confidence: 99%